The (010) Surface of the Al45Cr7 Complex Intermetallic Compound: Insights from Density Functional Theory. Issue 14 (4th June 2020) - Brix, Florian; Simon, Romain; Gaudry, Émilie
Abstract : The Al45 Cr7 compound is considered to exhibit an approximant structure of the icosahedral Al4 Cr phase. Its (010) surface has been investigated in detail using density functional calculations. Surface energy calculations show that the stable terminations result from a cleavage of the crystal between adjacent atomic planes, in agreement with the layered structure of the compound. The integrity of the icosahedral atomic arrangements (icosahedral clusters) found in the bulk structure, is predicted to be removed at the surface. This result is in contrast to what has been previously concluded for the (010) surface of the Al13 Fe4 quasicrystal approximant. Our findings are discussed in relation to the bonding network in the compound, calculated using the Crystal Orbital Hamiltonian Population approach, as possible reasons for such contrasted behavior. Abstract :